Creativity as action: findings from five creative domains - Glaveanu, Vlad; Lubart, Todd; Bonnardel, Nathalie; Botella, Marion; de Biaisi, Pierre-Marc; Desainte-Catherine, Myriam; Georgsdottir, Asta; Guillou, Katell; Kurtag, Gyorgy; Mouchiroud, Christophe; Storme, Martin; Wojtczuk, Alicija; et al. (Frontiers in Psychology, 2013)
The present paper outlines an action theory of creativity and substantiates this approach by investigating creative expression in five different domains. We propose an action framework for the analysis of creative acts built on the assumption that creativity is a relational, inter-subjective phenomenon. This framework, drawing extensively from the work of Dewey (1934) on art as experience, is used to derive a coding frame for the analysis of interview material. The article reports findings from the analysis of 60 interviews with recognised French creators in five creative domains: art, design, science, scriptwriting, and music. Results point to complex models of action and inter-action specific for each domain and also to interesting patterns of similarity and differences between domains. These findings highlight the fact that creative action takes place not ‘inside’ individual creators but ‘in between’ actors and their environment. Implications for the field of educational psychology are discussed.